Innovations in intracranial aneurysm treatment: a pilot study on the Choydar flow diverter - Liu, Changya; Cai, Yike; Zang, Chunguang; Guo, Kaikai; Hu, Xuebin (Frontiers in Neurology, 2024)
Background The flow diverter (FD) has emerged as a promising treatment option for intracranial aneurysms. Recently, a novel flow-diverting stent, the Choydar FD device, has been developed within our nation. Objective To introduce the newly developed Choydar FD device and present our preliminary clinical experience with its application in the treatment of intracranial aneurysms. Methods A total of 23 patients with 23 unruptured intracranial aneurysms, comprising 20 (87.0%) aneurysms located at the internal carotid artery and 3 (13.0%) at the vertebral artery, were treated with the Choydar FD device between December 2021 and April 2022. Patient baseline data, clinical and angiographic outcomes were collected and analyzed. Results The Choydar FD device was successfully deployed in all patients (100%), with 18 aneurysms (78.3%) additionally treated with coils. One patient experienced an ischemic event with sensory disturbance during the perioperative period. At the 1-year follow-up, all patients demonstrated good clinical outcomes. Of the 23 aneurysms with available angiographic follow-up, 22 (95.7%) achieved complete occlusion, and one patient exhibited in-stent stenosis without neurological deficits. Conclusion The initial clinical results of the Choydar FD device are encouraging, and it appears to be a useful option for treating intracranial aneurysms with acceptable efficacy and safety. Future studies with larger sample sizes and longer follow-up durations are warranted to validate these findings.